Long-term effects of bone char and lignocellulosic biochar-based soil amendments on phosphorus adsorption–desorption and crop yield in low-input acidic soils - Wakweya, Temsegen; Nigussie, Abebe; Worku, Gebeyanesh; Biresaw, Armaye; Aticho, Abebayehu; Hirko, Obsu; Ambaw, Gebermedihin; Mamuye, Melkamu; Dume, Bayu; Ahmed, Milkiyas (Wiley, 2022)
Although the addition of biochar has been shown to reduce the phosphorus (P) adsorption capacity of soil, quantitative evidence of this has mainly been provided by incubation experiments and it is, therefore, essential to conducting long-term field trials to draw general conclusions. It is largely unknown whether bone char has a greater effect than lignocellulosic biochar on P adsorption-desorption processes and crop yield. The aim of this study was to determine the long-term (8 years) effect of bone char and biochar on P adsorption-desorption and crop yield in low-input acidic soils. The results showed that bone char decreased the maximum P adsorption capacity (Qm) by 10% and increased the desorption capacity (Ds) by 150% compared with the control (i.e. without a soil amendment). The desorption ratio was highest for the bone char treatment (10.3%) and three times more than the control. Plant-available P was seven times greater under bone char than the control. There was no variation in adsorption-desorption characteristics, desorption ratio and plant-P available content between bone char and lignocellulosic biochar treatments. The average yield increment following the application of bone char and biochar was 1.7 and 1.4 Mg ha−1 for maize and 1.8 and 1.9 Mg ha−1 for soya bean, respectively. Despite the low application rate (4 t ha−1 year−1), these findings demonstrated that the long-term application of bone char and biochar-based amendments enhanced P availability in low-input cropping systems, mainly by altering the P adsorption and desorption capacity of soils.